CRIMINAL COMPLIANCE AS A CRIMINOLOGICALPOLITICAL DEVICE - Espinoza Bonifaz, Augusto Renzo (2022)
This revision article is dedicated, in theintroduction, to describe the problem identified by the author with respect to the institution of Criminal Compliance, as well as to determine its objectives. Then, various concepts about Criminal Compliance, Criminology, Criminological Policy, and some relevant criminological theories to prevent corporate crime are exposed, also demonstrating the relationships that exist between these concepts. Subsequently, the author rehearses and substantiates various solution proposals for each of the problems identified in the introduction. Finally, the main conclusions that have been reached as a result of the investigation were provided